Optimalisasi Kompetensi Manajerial Mahasiswa Administrasi Kesehatan melalui Pelatihan Penyusunan Alur Pelayanan - Kalsum, Ummu; Rahmilah, Mitha; Azizah, Andi Nurul; Mappanyukki, Andi Atssam; Haeril, Haeril (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aims to optimize the managerial competencies of students in the Health Administration Study Program through training in the preparation of health service flowcharts using Microsoft Visio. The implementation methods include counseling, training, case study-based flowchart preparation practice, and mentoring. Evaluate activities using a pre-test and post-test design aimed at measuring participants' knowledge levels. This activity involved 21 students who participated in training at the Computer Laboratory of the Faculty of Sports Science and Health, Makassar State University. The evaluation results showed that before the training, 42.9% of participants had a good level of knowledge, which increased to 95.2% after the training. Conversely, participants with poor knowledge decreased from 57.1% to 4.8%. The Wilcoxon test results show a significant increase in knowledge before and after training. This training also improved students' skills in systematically organizing and visualizing health service flows. Thus, the training activity proved effective in improving students' managerial competencies, particularly in process analysis and visualization of health service flows. Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengoptimalkan kompetensi manajerial mahasiswa Program Studi Administrasi Kesehatan melalui pelatihan penyusunan alur pelayanan kesehatan menggunakan Microsoft Visio. Metode pelaksanaan meliputi penyuluhan, pelatihan, praktik penyusunan flowchart berbasis studi kasus, serta pendampingan. Evaluasi kegiatan menggunakan desain pre-test dan post-test yang bertujuan untuk mengukur tingkat pengetahuan peserta. Kegiatan ini melibatkan 21 mahasiswa yang mengikuti pelatihan di Laboratorium Komputer Fakultas Ilmu Keolahragaan dan Kesehatan Universitas Negeri Makassar. Hasil evaluasi menunjukkan bahwa sebelum pelatihan, peserta dengan tingkat pengetahuan baik sebesar 42,9% dan meningkat menjadi 95,2% setelah pelatihan. Sebaliknya, peserta dengan pengetahuan kurang menurun dari 57,1% menjadi 4,8%. Hasil uji Wilcoxon menunjukkan adanya peningkatan pengetahuan yang signifikan sebelum dan sesudah pelatihan. Pelatihan ini juga meningkatkan keterampilan mahasiswa dalam menyusun dan memvisualisasikan alur pelayanan kesehatan secara sistematis. Dengan demikian, kegiatan pelatihan terbukti efektif dalam meningkatkan kompetensi manajerial mahasiswa, khususnya dalam analisis proses dan visualisasi alur pelayanan kesehatan.